Penguatan Karakter Siswa Madrasah Tsanawiyah Melalui Pembelajaran Berbasis Integrasi Sains dan Islam - Mahbubah, Khoiro; Santoso, Agus; Prafianti, Rayinda Aseti; Rahmawati, Santi (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2025)
The era of globalization affects the world of education including student behavior, this is reflected in the decline in the attitudes or characters of school students at MTs Al Karimi 1 Gresik, far from the culture of Islamic boarding schools in the previous generation. To overcome these problems, community service activities aim to develop teacher professionalism through the application of integrated science and Islamic learning by being implemented in the form of interactive training and mentoring involving MTs Al Karimi 1 Gresik teachers. The method of community service activities with the ICARE model (Introduction, Connection, Application, Reflection and Extend) is structured and systematic with the stages of introducing concepts, connecting with teaching experience, preparing learning plans, reflection and independent application in class. The results of the evaluation of community service activities show that teachers' understanding of the application of integrated science and Islamic learning has a positive impact and is able to prepare contextual learning plans and teachers are confident and consistent in implementing integrated science and Islamic learning. The findings of this community service activity show the importance of sustainable activities and follow-up with the learning community to develop sustainable learning, especially schools in Islamic boarding schools.